Pengaruh Celebrity Endorser, Brand Image, dan Elektronic Word of Mouth terhadap Pembelian Pada Pengguna E-Commerce Shopee di Indonesia - Muhammad Fauzi Amrullah (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2021)
This study aims to examine the influence of the variables Celebrity Endorser, Brand Image, and Electronic Word of Mouth on Purchasing Decisions among Shopee e-commerce users in Indonesia. This research is a causal quantitative research and data collection tools using a closed questionnairevia google form. The population in this study were Indonesians who shop using Shopee and the number of samples in this study were 80 people. The sampling technique used in this reseach isnon-probability sampling with purposive sampling method. The analysis used is multiple linear regression test. The data analysis technique uses the IBM SPSS version 21 program.The results of the analysis show that the variables of Celebrity Endorser, Brand Image, and Electronic Word of Mouth have a positive and significant effect on Purchasing Decisions on Shopee e-commerce users in Indonesia and the coefficient of determination (R2) by 0.603 or 60.3%.